The pre-participation examination - Kelsick, W. E. (IAAF Report on 15th NACACTFCA Congress 15th NACACTFCA Congress on Endurance, Boca Chica, Dominican Republic, October 2005, 2006)
Author shows how a pre-participation examination can help avoid injury and improve performance in track and field athletes.